2021
DOI: 10.3389/fimmu.2021.702785
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Pro-Resolving Mediators Mitigate Cancer-Related Inflammation: Role of Tumor-Associated Macrophages and Therapeutic Opportunities

Abstract: Inflammation is a fundamental physiological response orchestrated by innate immune cells to restore tissue homeostasis. Specialized pro-resolving mediators (SPMs) are involved in active resolution of inflammation but when inflammation is incomplete, chronic inflammation creates a favorable environment that fuels carcinogenesis and cancer progression. Conventional cancer therapy also strengthens cancer-related inflammation by inducing massive tumor cell death that activate surrounding immune-infiltrating cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 206 publications
(323 reference statements)
0
30
0
1
Order By: Relevance
“…Also, we observed that the anti-tumor effect of SuperMApo was dependent on existing host immune cell response specific to cancer cells. Myeloid cells, and macrophages even more, are both sentinel cells controlling tissue hemostasis as well as regulators of pro-tumor inflammation due to their plasticity ( 52 , 53 ). Indeed, macrophages have pro- and also anti-tumor properties ( 18 , 52 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, we observed that the anti-tumor effect of SuperMApo was dependent on existing host immune cell response specific to cancer cells. Myeloid cells, and macrophages even more, are both sentinel cells controlling tissue hemostasis as well as regulators of pro-tumor inflammation due to their plasticity ( 52 , 53 ). Indeed, macrophages have pro- and also anti-tumor properties ( 18 , 52 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells, and macrophages even more, are both sentinel cells controlling tissue hemostasis as well as regulators of pro-tumor inflammation due to their plasticity ( 52 , 53 ). Indeed, macrophages have pro- and also anti-tumor properties ( 18 , 52 54 ). Tumor-associated macrophages (TAM) are associated with a poor prognosis in cancer ( 18 , 25 , 29 , 52 , 53 , 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is the basic physiological response of the body to external stimuli; it is usually coordinated by immune cells to restore homeostasis [ 110 ]. In ACI, however, hyperactivated microglia produce massive amounts of inflammatory cytokines, causing inflammatory storms and eventually aggravating disease progression [ 111 ].…”
Section: Snhg4 In Cell Lines Studiesmentioning
confidence: 99%
“…In the subthreshold inoculum model, instead of suppressing tumor growth, chemotherapy promoted tumor growth in small or dormant tumors via tumor-promoting debris [ 1 , 3 ]. Similarly, chemotherapy-generated tumor cell “debris” (apoptotic and necrotic cells and cell fragments) promotes cancer progression and metastasis via stimulating an eicosanoid-driven cytokine storm of pro-inflammatory and pro-angiogenic mediators [ 1 , 2 , 14 , 38 , 39 , 57 , 76 ], polarizing tumor-associated macrophages (TAMs) as well as inducing immunosuppression and limiting anti-tumor immunity [ 24 , 77 , 78 ]. Thus, new approaches to stimulate the clearance of tumor cell debris are urgently needed [ 1 , 21 , 40 , 78 80 ].…”
Section: Chemotherapy-stimulated Cancermentioning
confidence: 99%